Elevated accuracy in recognition of subliminal happy facial expressions in patients with panic disorder after psychotherapy - Qian, Zirong; Yang, Yunbo; Domschke, Katharina; Gerlach, Alexander L.; Hamm, Alfons; Richter, Jan; Herrmann, Martin J.; Deckert, Jürgen; Arolt, Volker; Zwanzger, Peter; Lotze, Martin; Pfleiderer, Bettina; et al. (Frontiers in Psychiatry, 2024)
Individuals with anxiety disorders (ADs) often display hypervigilance to threat information, although this response may be less pronounced following psychotherapy. This study aims to investigate the unconscious recognition performance of facial expressions in patients with panic disorder (PD) posttreatment, shedding light on alterations in their emotional processing biases. Patients with PD (n=34) after (exposure-based) cognitive behavior therapy and healthy controls (n=43) performed a subliminal recognition task. Emotional facial expressions (fearful, happy, or mirrored) were displayed for 33 ms and backwardly masked by a neutral face. Participants completed a forced choice task to discriminate the briefly presented facial stimuli and an uncovered condition where only the neutral mask was shown. We conducted a secondary analysis to compare groups based on their four possible response types under the four stimulus conditions and examined the correlation of the false alarm rate for fear responses to non-fearful (happy, mirrored, and uncovered) stimuli with clinical anxiety symptoms. The patient group showed a unique selection pattern in response to happy expressions, with significantly more correct "happy" responses compared to controls. Additionally, lower severity of anxiety symptoms after psychotherapy was associated with a decreased false fear response rate with non-threat presentations. These data suggest, that patients with PD exhibited a "happy-face recognition advantage" after psychotherapy. Less symptoms after treatment were related to a reduced fear bias. Thus, a differential facial emotion detection task could be a suitable tool to monitor response patterns and biases in individuals with ADs in the context of psychotherapy.